2014
DOI: 10.2214/ajr.13.11492
|View full text |Cite
|
Sign up to set email alerts
|

Safety of an IV β-Adrenergic Blockade Protocol for Heart Rate Optimization Before Coronary CT Angiography

Abstract: This study showed that high doses of i.v. metoprolol can be used effectively and with a low rate of major complications to control heart rate before coronary CT angiography in correctly screened patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Many centers are reluctant to administer IV medication for HR control during coronary CTA owing to the fear from potential side effects. A recent study by Kassamali et al 19 reported minor complications (transient hypotension) related to IV metoprolol administration only in 1.47% and major complications (not resolving with observation of analgesia) in 0.44% of patients who underwent coronary CTA. These results demonstrate that IV metoprolol is a safe drug to use for this purpose in patients with normal left ventricular function although the study was underpowered to assess for rare major complications.…”
Section: Discussionmentioning
confidence: 97%
“…Many centers are reluctant to administer IV medication for HR control during coronary CTA owing to the fear from potential side effects. A recent study by Kassamali et al 19 reported minor complications (transient hypotension) related to IV metoprolol administration only in 1.47% and major complications (not resolving with observation of analgesia) in 0.44% of patients who underwent coronary CTA. These results demonstrate that IV metoprolol is a safe drug to use for this purpose in patients with normal left ventricular function although the study was underpowered to assess for rare major complications.…”
Section: Discussionmentioning
confidence: 97%
“…Recent investigations show that the use of intravenous β-adrenergic blockade before coronary CT angiography is a safe prophylactic tool to optimize the heart rate [7,8]. Aggarval et al have presented similar results concluding that betablocker premedication does not increase the frequency of allergic reactions from coronary CT angiography [9].…”
Section: Beneficial Effects Of Beta Blockersmentioning
confidence: 94%
“…On the other hand more recent papers dealing with this topic did not confirm negative influences from the intake of beta blockers [6][7][8][9]. For example, it could be shown that both isoprenaline and salbutamol act as β 2 -adrenoceptors to suppress IgE-mediated mediator release from cultured human mast cells [6].…”
Section: Beneficial Effects Of Beta Blockersmentioning
confidence: 99%
“…Although β-blocker may reduce the extent and severity of perfusion abnormalities [ 187 ], one study indicates that diagnostic accuracy of PET perfusion imaging was maintained in patients who received i.v. β-blocker to slow down the heart rate before CCTA [ 188 ]. Proper indications and possible contraindications, such as contrast allergy, should be reviewed separately for PET and CT studies [ 176 ].…”
Section: Perspectives For Pet Mpimentioning
confidence: 99%